DEVELOPING AN ESP-BASED LANGUAGE LEARNING ENVIRONMENT TO HELP STUDENTS IMPROVE CRITICAL THINKING SKILLS IN WRITTEN OUTPUT - Shikina Aleksandra Aleksandrovna; Odiljonova Shirin Isroiljon qizi; Xosilova Solixabonu Ulug’bek qizi (Modern American Journals, 2025)
This study investigates how an ESP-based language learning environment can enhance students’ critical thinking skills through written output. Drawing on a review of open-access literature, the paper analyzes international case studies from Vietnam, Indonesia, and other regions to explore effective instructional strategies such as Task-Based Language Teaching (TBLT), Content-Based Instruction (CBI), and ICT integration. Findings highlight that writing, when supported by context-specific materials, collaborative learning, and metacognitive activities, becomes a powerful tool for developing analytical and reflective thinking—skills essential for academic and professional success, including in Uzbekistan.
Keywords: ESP, critical thinking, written output, Task-Based Language Teaching, ICT, higher-order thinking, academic writing